IgG subclass and light chain distribution of anticardiolipin and anti-DNA antibodies in systemic lupus erythematosus. Issue 4 (April 1988) - Gharavi, A E; Harris, E N; Lockshin, M D; Hughes, G R; Elkon, K B
Abstract : The IgG subclass and light chain distribution of anticardiolipin and anti-DNA antibodies were determined in serum samples from patients with systemic lupus erythematosus. With an enzyme linked immunosorbent assay (ELISA) and mouse monoclonal antibodies to individual subclasses, significant differences in the distributions of IgG2, IgG3, and IgG4 subclasses were observed between anticardiolipin and anti-DNA antibodies. Whereas anti-DNA antibodies were predominantly IgG1 and IgG3, all subclasses of anticardiolipin were detected with a prevalence ranging from 34% (IgG3) to 57% (IgG1). Clinical complications were found slightly more frequently (83%) in patients with sera containing the non or weak complement fixing subclasses (IgG2 and IgG4) than in patients with sera containing complement fixing (IgG1 and IgG3) subclasses (62%). Light chain analysis by ELISA showed a trend towards use of kappa chains for anti-DNA and lambda chains for anticardiolipin antibodies. These findings further emphasise the differences between anti-DNA and anticardiolipin antibodies in terms of their origins and potential mechanisms for producing tissue injury.